(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
Socialised medicine in Europe is entering an algorithmic era. The Artificial Intelligence (AI) Act (Regulation (EU) 2024/1689) introduces horizontal, risk-based rules that coexist with sectoral regimes for medical devices-Medical Device Regulation (MDR) / In Vitro Diagnostic Medical Device Regulation (IVDR). In Italy, Law 24/2017 (Gelli Bianco) structures professional and organisational liability. We examined how these regimes interact in clinical practice and which governance, auditing and insurance tools make AI both safe and equitable. We conducted a multidisciplinary doctrinal and policy analysis of EU instruments (AI Act, MDR/IVDR, Medical Device Coordination Group-MDCG 2019 11 rev.1 and MDCG 2025 6), European Medicines Agency (EMA)’s 2024 Reflection Paper on the medicinal product lifecycle, World Health Organization (WHO) ethics guidance and Organisation for Economic Co-operation and Development (OECD) reports, complemented by a focused scoping of peer reviewed literature on algorithmic auditing, fairness and medico legal accountability. We mapped obligations along the AI lifecycle, built role responsibility matrices and derived an operational co regulation cycle. We identify a dual track compliance architecture: MDR/IVDR ensure clinical safety and performance; the AI Act adds data governance, logging, human oversight, fairness and post market monitoring, with staged application (2025-2027). We specify responsibilities for manufacturers, physicians and facilities and formalise algorithmic audits (pre market/post market/extraordinary) with transparent reporting. We link these to adaptive Health Technology Assessment (HTA) and product liability reform (Directive (EU) 2024/2853). We conclude that dynamic co regulation-living guidelines, lifecycle auditing, transparent logs and risk-based insurance-can align innovation with equity, safety and accountability.